O envelhecer da mulher que não experimentou a maternidade - Conrado, Vivian Balem (2017)
Longevity has brought about a new resizing of the aging of women, as new opportunities have been presented with the aim of expanding their social, affective, emotional, physical space and their roles as new ways of experiencing knowledge and learning. The number of elderly women who did not have children grows in contemporary society. The topic of maternity mobilizes women emotionally and socially, since not having children, by choice or circumstances, implies not performing a social function still charged as a woman's role. To know how the process of aging grows in the face of the experience of not being a mother is to unveil the normative and not normative process about the elderly woman. The objective of the study was to know t he aspects of the aging process of women who did not experience motherhood. It is a descriptive research with a qualitative approach. The participants of the study were 13 women 60 years old or older who did not have children, and who are part of a coexistence group living in the urban area of Passo Fundo, RS. The choice of participants took place intentionally, and the procedure of data collection in the form of semi-structured interviews, from June to September 2016. The content analysis allowed the construction of two categories: a) conceptions about aging, which Presents the ideation of a successful process and bleak perspective of aging; B) perspective of care in old age. The results show fears and uncertainties of women with the possibility of being cared for or need help, in the face of the absence of children. The perceptions about this experience reveal positive and negative aspects, present conceptions and ideations of a successful aging process, as well as negative perspectives of this same process.